Diagnostic Value of a Protocolized In-Depth Evaluation of Pediatric Bone Marrow Failure: A Multi-Center Prospective Cohort Study - Atmar, Khaled; Ruivenkamp, Claudia A. L.; Hooimeijer, Louise; Nibbeling, Esther A. R.; Eckhardt, Corien L.; Huisman, Elise J.; Lankester, Arjan C.; Bartels, Marije; Santen, Gijs W. E.; Smiers, Frans J.; van der Burg, Mirjam; Mohseny, Alexander B. (Frontiers in Immunology, 2022)
Background: Severe multilineage cytopenia in childhood caused by bone marrow failure (BMF) often represents a serious condition requiring specific management. Patients are at risk for invasive infections and bleeding complications. Previous studies report low rates of identifiable causes of pediatric BMF, rendering most patients with a descriptive diagnosis such as cytopenia of unknown origin or aplastic anemia (AA). Methods: We conducted a multi-center prospective cohort study in which an extensive diagnostic approach for pediatric patients with suspected BMF was implemented. After exclusion of malignant and transient causes of BMF, patients entered thorough diagnostic evaluation including bone marrow analysis, whole exome sequencing (WES) including copy number variation (CNV) analysis and/or single nucleotide polymorphisms (SNP) array analysis. In addition, functional and immunological evaluation were performed. Here we report the outcomes of the first 50 patients (2017-2021) evaluated by this approach. Results: In 20 patients (40%) a causative diagnosis was made. In this group, 18 diagnoses were established by genetic analysis, including 14 mutations and 4 chromosomal deletions. The 2 remaining patients had short telomeres while no causative genetic defect was found. Of the remaining 30 patients (60%), 21 were diagnosed with severe aplastic anemia (SAA) based on peripheral multi-lineage cytopenia and hypoplastic bone marrow, and 9 were classified as unexplained cytopenia due to absence of disease-specific abnormalities in any diagnostic test. In 22/30 (73%) patients with unknown cause, treatment with hematopoietic stem cell transplantation (HSCT) was needed, while only 6/20 (30%) patients with an identified cause for BMF were transplanted. Conclusion: We conclude that a standardized in-depth diagnostic protocol as presented here, can increase the frequency of identifiable causes within the heterogeneous group of pediatric BMF. We underline the importance of full genetic analysis complemented by functional tests of all patients as genetic causes are not limited to patients with typical (syndromal) clinical characteristics beyond cytopenia. In addition, it is of importance to apply genome wide genetic analysis, since defects in novel genes are frequently discovered in this group. Identification of a causal abnormality consequently has implications for the choice of treatment and in some cases prevention of invasive therapies.